Risk factors for coronary heart disease in individuals aged ≥40 at Samarinda General Hospital Medika Citra. - Aliansyah, Saniah; Sinaga , Tumpak; Lepong, Abida (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Coronary heart disease is a dysfunction of the heart due to narrowing or blockage of the coronary arteries, if blood flow to the heart muscle is blocked, the heart does not get enough oxygen and nutrients. The peak incidence of CHD is 60-70 years old, but the more age the CHD sufferers are younger. Objective : The purpose of this study was to determine the risk factors for coronary heart disease in the age group ≥40 years old. Research Methods/ Implementation Methods : The method used is an analytical survey with Case Control approach. The study sample consisted of 60 people consisting of 30 case groups and 30 control groups with matching using age and gender collected by purposive sampling technique. Data analysis using Chi Square test with error degree = 0.05. Results : The results showed that there was a relations between hypertension (p = 0.018 and OR = 4.0; 95% CI = 1.272-12.578) diabetes mellitus (p = 0.011 and OR = 4.0; 95% CI 1.372-11.839) high cholesterol ( p = 0.025 and OR = 4.3, 95% CI 1.20315.605) with the incidence of coronary heart disease at Samarinda Medika Citra General Hopital in 2018. Conclusion/Lesson Learned : The peak incidence of CHD is 60-70 years old, but the more age the CHD sufferers are younger.